Wetland Tourism Marketing: The Influence of Experience Dimensions and Memorable Tourism Experience on Tourist Loyalty of the Bakut Island Nature Tourism Park, Indonesia - Naparin, Muhammad; Aryadi, Mahrus; Prihatiningrum, R. R. Yulianti; Suyatnob, Suyatno (International Review of Management and Marketing, 2024)
In the tourism sector, wetlands provide a wealth of biodiversity and diverse landscapes including natural resource conservation tourism (flora fauna). In this context, marketing is needed to provide sustainable competitiveness for natural tourism parks. This study aimed to test four dimensions of tourist experience (educational, aesthetic, entertainment, escapism) on memorable tourism experiences (MTE), and to test the influence of MTE on tourist loyalty (TL). This study used a quantitative method and SmartPLS 4.1 for statistical analysis. Respondents were tourists who had visited the Bakut Island Nature Tourism Park, Indonesia. The results of the study showed that educational experience (EduEx), aesthetic experience (AesEx), entertainment experience (EntEx), and escapism experience (EscEx) had a significant positive effect on MTE, and MTE had a significant positive effect on TL. The urgency and implications of this study were to design the four dimensions of experience that influence TL that provide positive stimulus to tourist behavior for biodiversity conservation both during and after the visit in achieving sustainable development goals. The originality of this study was to test the antecedents of TL from the customer experience perspective, as well as to provide a clear substantive distinction between the dimensions of tourist experience and memorable tourism experiences.